2012
DOI: 10.1155/2012/471823
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Reverse Endothelial Progenitor Cell Dysfunction in Diabetes

Abstract: Bone-marrow-derived cells-mediated postnatal vasculogenesis has been reported as the main responsible for the regulation of vascular homeostasis in adults. Since their discovery, endothelial progenitor cells have been depicted as mediators of postnatal vasculogenesis for their peculiar phenotype (partially staminal and partially endothelial), their ability to differentiate in endothelial cell line and to be incorporated into the vessels wall during ischemia/damage. Diabetes mellitus, a condition characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Our findings suggest a potential therapeutic value of this triterpenoid compound for the treatment of atherosclerosis. The capacity of EPCs to differentiate into endothelial cells and participate in vascular repair and an extensive body of research showing that dysfunctional EPCs have defects in angiogenic properties and can contribute to vascular and cardiovascular diseases underscores the importance of developing strategies to improve EPC function [25,26]. Genetic modification of EPCs with vascular endothelial growth factor (VEGF) improved their proliferation, adhesion and incorporation into endothelial cell monolayers, and improved neovascularization and blood flow recovery in a mouse model [27].…”
Section: Ilk Regulates Akt/gsk-3β Phosphorylation and The Expression mentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest a potential therapeutic value of this triterpenoid compound for the treatment of atherosclerosis. The capacity of EPCs to differentiate into endothelial cells and participate in vascular repair and an extensive body of research showing that dysfunctional EPCs have defects in angiogenic properties and can contribute to vascular and cardiovascular diseases underscores the importance of developing strategies to improve EPC function [25,26]. Genetic modification of EPCs with vascular endothelial growth factor (VEGF) improved their proliferation, adhesion and incorporation into endothelial cell monolayers, and improved neovascularization and blood flow recovery in a mouse model [27].…”
Section: Ilk Regulates Akt/gsk-3β Phosphorylation and The Expression mentioning
confidence: 99%
“…EPC mobilization by treatment with AMD3100 and transfer of bone marrow EPCs was shown to improve plaque regression in a mouse model of atherosclerosis [2]. Several strategies aimed at improving autologous EPC function by ex vivo conditioning with growth factors/chemoattractants such as SDF-1α, VEGF, and interleukin-8, antioxidants, hormones and clinically available drugs such as statins and ACE-inhibitors have been shown to improve EPC function [26]. In the present study, we explored the effect of tripterine on ox-LDL induced EPC dysfunction and showed its ability to increase proliferation, migration and the adhesive abilities of EPCs as well as attenuating ox-LDL induced EPC apoptosis.…”
Section: Ilk Regulates Akt/gsk-3β Phosphorylation and The Expression mentioning
confidence: 99%
“…Data have proven that the number and functions of EPCs are impaired by cardiovascular risk factors like hypertension, hyperglycemia and inflammatory mediators, etc. (Lee et al, 2011;Petrelli et al, 2012;Westerweel and Verhaar, 2009). Tumor necrosis factor-α (TNF-α) is a key inflammatory cytokine which can reduce the number and impair the function of EPCs (Xu et al, , 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…This newly discovered diabetic complication of the bone marrow is associated with a reduced stem cell ability to be mobilized from bone marrow in diabetic individuals. This pathophysiological state has been recently named 'stem cell mobilopathy' [6] and may be responsible for an altered arterial remodeling, an accelerated atherosclerosis and a poor response to ischemia because of the reduced turnover of peripheral vascular progenitors of bone marrow origin [7]. The immune system may be affected as well, both for the onset of an altered peripheral cell phenotype or because of a reduced number in the periphery of cells with anti-inflammatory/regulatory properties [8].…”
Section: Commentarymentioning
confidence: 99%